An analysis on the Training & Development program of ACI Logistics Limited (Shwapno) by linking up theoretical knowledge with practical experiences - Saif, Sadrina Bintae (BRAC University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.